O processo de autoavaliação institucional proposto no Sistema Nacional de Avaliação da Educação Superior (SINAES) para as instituições públicas e privadas - Ribeiro, Elisa Antonia (2010)
This thesis deals with the process of effecting the proposed institutional self-evaluation by the Sistema Nacional de Avaliação da Educação Superior (SINAES), held in Higher Education Institutions (HEIs) Private and Public perceptions of its actors, and the amendment of the aspects of teaching performance in classroom from the results of the evaluation teacher. The objectives were: to understand the changing political, social and economic that have occurred in recent decades, with the backdrop of the reconfiguration of the state and its relationship with current assessment policies for higher education, understand the formation of the field of evaluation of higher education highlighting the area of institutional assessment, analyzing the origins of systems of higher education until the actual moment of implementation of the SINAES; compare the effective processes of institutional self-evaluation in Public and Private HEIs and to determine which aspects of educational performance are being modified from the results of the evaluation teaching. The assumptions were that SINAES to determine the requirement of including systematic institutional self-evaluation led to the expansion of scientific evaluation in the area of IES and teaching performance is being rethought in light of the results of teacher assessment. The categories used were: the importance of evaluation of institutions of higher education, deployment and current stage of the process of selfassessment in HEIs; difficulties of operation, institutional benefits, use of results, participation and incorporation of results of self-assessment in educational performance. We made a detailed theoretical research on the constitution of the State Assessor, training for the field of institutional assessment and the formulation of Law 10.861 of April 14, 2004. In the empirical field, we conducted a comparative study on the process of realization of self-evaluation in two institutions of higher education. The research involved in private HEIs, two leaders, 56 teachers and 318 students, in public HEIs, four officers, 10 teachers and 35 students, included also the study of the Institutional Self-evaluation of projects and Final Reports of the first and second cycles HEIs. The results indicated that the two IES, the process of self-assessment is developing according to the following phases: in 2004, a period of collective construction of the proposed self-assessment; from 2005 to 2006, a period of an institutional "euphoria", overwhelmingly, by the strong performance of the CPA; in the setting of the institution, end 2008 to 2009, the issue of self-assessment loses focus internally, influenced by new guidelines for carrying out the evaluation of higher education determined by the Ministry of Education. We also confirm the assumption that some aspects of the classroom related to teaching performance are being altered and rethought in light of the results of teacher assessment and evaluation of current policies for higher education.